Beginning Windows 8 Application Development - Novák, István; Arvai, Zoltan; Balássy, György; Fulop, David; Árvai, Zoltán; Nov?k, Istv?n; Bal?ssy, Gy?rgy (Wrox Programmer to Programmer, 2012)
Learn to use exciting new development tools and create applications for Windows 8 If you're a beginning developer, there's no better place to get up to speed on the Windows 8 SDK than this Wrox guide. A team of Microsoft experts provides a complete course in Windows 8 programming, helping you take full advantage of the innovative new SDK. Written in an easy-to-read style, this book is packed with reusable examples that showcase the endless possibilities of the Windows SDK and also introduces the new Windows 8 app store. It explains how to set up the development environment and covers user interface design, using special effects and graphics, working with C# and C++, and much more. Provides a complete introduction to the Windows SDK and Windows 8, starting with setting up the development environment and building your first application Covers user interface design, touch- and event-driven design elements, leveraging windows-based services, and offline application development with HTML 5 Explores creating C# applications for the Windows 8 system, XNA 4 and Silverlight 5 considerations, and the role of C++ Shows how to debug, certify and deploy your applications Introduces the new Windows 8 app store and offers advice on marketing your apps Beginning Windows 8 Application Development is perfect for anyone who's ready to get started developing apps for the exciting new Windows 8 OS.